Om Fordelagtigheden af Sukkerroedyrkningen i Danmark. Foredrag, d. 21de Febr. 1872. - St. Lorenzen, W. (Tidsskrift for Landøkonomi, 2018)
Om Fordelagtigheden af Sukkerroedyrkningen i Danmark. Foredrag, d. 21de Febr. 1872.